THE ISLAMIC STATE AND JABHAT ALNUSRA; NEW ACTORS IN LEBANON? (Journal of the Spanish Institute for Strategic Studies, 2018)
From a historical perspective, Lebanon’s social context has long beenconducive to the emergence and development of Sunni jihadism, butthe movement was too weak to challenge the status quo. However, theSyrian Civil War has changed the balance of power, putting Hezbollahon the defensive and weakening the Future Movement´s Sunnileadership. This has allowed the Lebanese jihadists to cooperate withthe Islamic State and Jabhat al-Nusra, who see the Lebanese crisis asan extension of the Syrian war. As a result, they are playing an increasinglyprominent role in the neighbouring country in a bid to spreadviolence and overstretch the military capabilities of the Lebanese armyand Hezbollah.